PERAN AYAH DALAM MENDIDIK ANAK - Nahar, Muhammad Hasnan (Center of Gender Studies and Child of State Islamic Institute of Metro, 2023)
The absence of a father in the parenting process has resulted in several negative impacts and the emergence of various psychological problems. The institutionalization of gender roles within the family, promoted by patriarchal culture, is identified as one of the factors contributing to the lack of involvement of fathers in child-rearing. This research aims to explore and analyze the role of fathers in educating their children, as depicted in the teachings of the Quran.The research methodology employed involves textual analysis of Quranic verses related to the father's role in the context of child education. Utilizing a psychological approach focusing on dimensions of paternal interaction, paternal accessibility, and paternal responsibility, various roles that fathers can assume in educating their children are identified. These roles encompass the father's duty to impart religious knowledge, provide early education, and deliver sexual education. The Quran consistently emphasizes the pivotal role of fathers in shaping the character and morality of their children. Verses within the Quran address aspects such as guidance, exemplary behavior, responsibility, and supportive educational companionship. This study contributes to a deeper understanding of the father's role in child education from the perspective of the Quran.The practical implications of this research underscore the importance of implementing values derived from the Quran in the father's parenting style. It is hoped that such implementation will provide a strong foundation for the well-rounded and high-quality character formation of children. Keywords: Thematic Interpretation, Fatherless, Father's Role Abstrak Ketidakhadiran ayah dalam proses pengasuhan telah menimbulkan beberapa dampak buruk dan munculnya beberapa masalah psikologis. Pembakuan peran laki-laki dan perempuan dalam keluarga yang dipromosikan oleh budaya patriarki menjadi salah satu faktor tidak terlibatnya laki-laki dalam pengasuhan anak. Penelitian ini bertujuan untuk menggali dan menganalisis peran ayah dalam mendidik anak, sebagaimana tergambar dalam ajaran Al-Quran. Metode penelitian yang digunakan adalah analisis tekstual terhadap ayat-ayat Al-Quran yang berkaitan dengan peran ayah dalam konteks pendidikan anak. Dengan pendekatan psikologi mengenai dimensi mendidik anak: paternal interaction, paternal accesibility, dan paternal responsibility maka terdapat peran-peran yang ayah dapat lakukan untuk mendidik anak. Pertama peran ayah untuk mengajarkan ilmu agama, kedua peran ayah untuk memberikan pendidikan sejak dini, ketiga peran ayah untuk memberikan pendidikan seksual. Al-Quran secara konsisten juga telah menekankan pentingnya peran ayah dalam membentuk karakter dan moralitas anak-anak. Ayat-ayat tersebut mencakup aspek-aspek seperti bimbingan, keteladanan, tanggung jawab, dan pendampingan yang bersifat edukatif. Penelitian ini memberikan kontribusi terhadap pemahaman lebih lanjut tentang peran ayah dalam pendidikan anak menurut perspektif Al-Quran. Implikasi praktisnya adalah pentingnya implementasi nilai-nilai yang terkandung dalam Al-Quran dalam pola asuh ayah, dengan harapan dapat memberikan landasan yang kuat bagi pembentukan karakter anak yang seimbang dan berkualitas Kata kunci: Tafsir Tematik, Fatherless, Peran Ayah